2018
DOI: 10.3390/ph11010028
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Chitosan-Coated PLGA Nanoparticles for Pulmonary Delivery of Tobramycin for Cystic Fibrosis

Abstract: (1) Background: Poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) loaded with Tobramycin were prepared using a solvent-evaporation method. (2) Methods: The NPs were coated with low molecular weight chitosan (LMWC) to enhance the mucoadhesiveness of PLGA-NPs. The following w/w ratios of tobramycin to LMWC were prepared: control (0:0.50), F0 (1:0.25), F0.5 (1:0.5), and F1 (1:1). (3) Results: The results showed that the size of the particles increased from 220.7 nm to 575.77 nm as the concentration of LMWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 45 publications
(49 reference statements)
2
30
0
Order By: Relevance
“…The cumulative % release after 72 hours was 92.62% for F2 this was in agreement with Jeong et al (2008b) and Song et al (2008) who stated that around 60% of drug is released in the first 24 h from PLGA followed by slow release over days. The release of drug in F3 is 78.3%, as noted it was slower than F2 due to coating with chitosan, as reported in previous studies which stated that chitosan coat hinder the release of the drug, also charge attraction between PLGA and chitosan played an important role in sustained drug release (Chen et al, 2016;Al-Nemrawi et al, 2018;Lu et al, 2019). The kinetics revealed that the in vitro release of F2 is zero-order kinetics, as the plots showed the maximum linearity (R 2 ¼ 0.951), in this case the rate of drug release is independent of its dissolved concentration in the release medium and is delivered at a constant rate over time (Majumder et al, 2018).…”
Section: In Vitro Drug Releasementioning
confidence: 52%
“…The cumulative % release after 72 hours was 92.62% for F2 this was in agreement with Jeong et al (2008b) and Song et al (2008) who stated that around 60% of drug is released in the first 24 h from PLGA followed by slow release over days. The release of drug in F3 is 78.3%, as noted it was slower than F2 due to coating with chitosan, as reported in previous studies which stated that chitosan coat hinder the release of the drug, also charge attraction between PLGA and chitosan played an important role in sustained drug release (Chen et al, 2016;Al-Nemrawi et al, 2018;Lu et al, 2019). The kinetics revealed that the in vitro release of F2 is zero-order kinetics, as the plots showed the maximum linearity (R 2 ¼ 0.951), in this case the rate of drug release is independent of its dissolved concentration in the release medium and is delivered at a constant rate over time (Majumder et al, 2018).…”
Section: In Vitro Drug Releasementioning
confidence: 52%
“…Moreover, electrostatic deposition could be applied for the formation of CCNs either in already formed negatively charged nanoparticles or during the formation of the nanoparticles ( Figure 7 ). Both approaches have been used to prepare coated polymeric nanoparticles, lipid nanoparticles and metal-based nanoparticles as well [ 183 , 186 , 188 , 189 , 206 , 207 , 208 ]. Especially, natural products such as curcumin [ 209 ] and resveratrol [ 192 ] were successfully encapsulated in chitosan-coated nanoformulations where the coating process was accomplished using pre-formed nanoemulsions and lipid microparticles, respectively.…”
Section: Chitosan-coated and Modified Chitosan Nanosystems Encapsumentioning
confidence: 99%
“…In theory, the larger the surface area, the more amino groups are present and therefore the more positive the zeta potential of the nanoparticle. The high surface charge of the nanoparticles also prevents particle aggregation in aqueous solution due to electrostatic repulsion [ 37 ]. The increase in zeta potential upon the coating of PEG may be due to multilayer deposition of PEG polymer during nanoparticle formation [ 13 ], which might cause interactions with the PLGA layer, exposing more of the cationic chitosan charge on the nanoparticle surface, as shown in Figure 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…Release behaviour is biphasic, with initial burst release caused by drug that is poorly bound by polymeric matrix or adsorbed on nanoparticle surface, while subsequent sustained release from PLGA core is further controlled by chitosan and PEG surface layers. PLGA degrades into its constituent co-polymers, lactic acid and glycolic acid, by hydrolysis of its ester linkages, while chitosan swells, providing a hydrogel-like layer which controls drug diffusion from the surface [ 37 ]. The profile of the microfluidic formulation displayed a slower release from 4 h to 12 h compared to the emulsification solvent evaporation prepared formulation.…”
Section: Resultsmentioning
confidence: 99%